The Pillars of the House Volume 2 - Yonge, Charlotte Mary (Saga Egmont, 2022)
\'The Pillars of the House Volume 2\' - or ´Under Wode, Under Rode´ - is the second instalment of English writer Charlotte Mary Yonge\'s story about the Underwood children. Set in the industrial town of Bexley, this Victorian family saga continues the story of the orphaned children as they struggle to survive and find their way in the world against all odds.A story of hope, love, sacrifice, and family, \'The Pillars of the House Volume 2\' will surely delight anyone interested in great family sagas.